INTRODUCING A NEW BUSINESS MODEL FOR THE PRIMARY HEALTHCARE DELIVERY IN SINGAPORE - Chua Swee Boon, Raymond (2006)
The current primary healthcare system faces a few main challenges, namely, an ageing population, increasing prevalence of chronic diseases and a more well-informed and affluent group of patients. This is not unique to Singapore only and a lot of other countries are also undergoing reform in their healthcare system to cope with these challenges.